Capital Structure and Social Signaling: A Dual Mechanism Analysis of Tax Aggressiveness in Emerging Markets - Happy Tatemba; Ika Prayanthi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Purpose This research investigates the influence of capital structure and social signaling on corporate tax behavior, specifically testing the Monitoring Hypothesis and the Substitution Effect within the Indonesia Stock Exchange. Design and Methodology A quantitative explanatory design was employed, analyzing 85 observations from non financial companies. Data were retrieved from the Bloomberg Terminal and annual reports. The Generalized Linear Model (GLM) with a Gaussian distribution and identity link function was utilized to examine the causal relationships between the Debt to Equity Ratio (DER), Social Scores, and the Effective Tax Rate (ETR), while controlling for governance and innovation metrics. Findings Empirical Results demonstrate that DER has a significant positive effect on ETR, confirming that leverage serves as an effective external monitoring mechanism that reduces tax aggressiveness. Conversely, Social Scores exhibit a significant negative impact on ETR, supporting the Substitution Effect. This suggests firms utilize high social performance as a reputational shield to mask tax avoidance, validating the